[Let's make a deal ; Ordinary people ; Two for the road [videorecording] - Lazaro, Cheche (The Probe Team ; [episode no. 130], 1990)
Deals with the negotiations of the PCGG on the ill-gotten wealth of the Marcoses; the causes of learning disabilities of children and the thirty-eight years of the singing career of the Reycard Duet.